Antibacterial Activity from Fraction of Liquid-Liquid Extraction in Temulawak Rhizome (Curcuma xanthorrhiza Roxb.) - Alighiri, Dante; Firnanda, Indah Putri; Abdullah, Ravely Adhitya; Widodo, Naufaldi Bani; Drastisianti, Apriliana (Walisongo Journal of Chemistry, 2024)
The rhizome of Temulawak (Curcuma xanthorrhiza Roxb) has been traditionally used to treat various ailments due to its rich content of curcumin, demethoxycurcumin, and bisdemethoxycurcumin. These compounds exhibit notable antioxidant and antibacterial properties. This study aimed to evaluate the antibacterial efficacy of Temulawak rhizome extracts in n-hexane, ethyl acetate, and methanol, focusing on Escherichia coli and Staphylococcus aureus. The extraction process involved successive maceration with each solvent. The antibacterial activity was tested using well diffusion and microdilution methods, determining minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Phytochemical screening revealed the presence of flavonoids, alkaloids, phenolics, steroids, and triterpenoids in the extracts. The results indicated that the n-hexane and ethyl acetate fractions exhibited intense antibacterial activity against Staphylococcus aureus, while all fractions showed potent activity against Escherichia coli. The MIC values ranged from 39.0625 to 625 ppm for Staphylococcus aureus and 39.0625 to 78.125 ppm for Escherichia coli, with MBC values generally higher than MIC values. These findings highlight the potential of Temulawak rhizome extracts as effective antibacterial agents.